PENGARUH NIM, DEP, LOANS, SIZE TERHADAP CAR PADA BANK UMUM DI BURSA EFEK INDONESIA - Karyawati, Danik; Marsana, Marsana; Sunarya, Sunarya; Sumawan, Sumawan (UNPERBA, 2022)
This research aims to analyze the influence of Net Interest Margin (NIM), Deposit Equity Ratio (DEP), Loans to Assets Ratio (LOANS), and bank size (SIZE) on the Capital Adequacy Ratio (CAR) in commercial banks listed on the Stock Exchange Indonesia (IDX). The data used is for 4 years, namely 2014, 2015, 2016, and 2017 with a total of 28 banking companies, using the pooled data method to obtain 112 data. The panel regression analysis method is used to test the relationship between these variables. The research results show that NIM has a significant positive influence on CAR, indicating that banks with higher net interest margins tend to have higher capital adequacy ratios. In addition, DEP and LOANS have an insignificant negative effect on CAR, indicating that banks with a higher deposit to equity ratio tend to have a lower CAR. The higher the LOA, the lower the CAR level. However, SIZE does not have a significant influence on CAR in this context. These findings provide important insights for bank management and regulators in understanding the factors that influence bank capital adequacy levels and designing appropriate policies to ensure financial system stability